Novel dynamic optical tweezers array generation using dark soliton control within an add/drop multiplexer - Pornsuwancharoen, N.; Tanaponjarus, C.; Dunmeekaew, U.; Yupapin, P. P. (My University, 2010)
We proposes a novel system of the optical tweezers array generation using dark soliton control within and add/drop filter. The dynamic tweezers are generated within an add/drop filter, where the number of tweezers within the add/drop filter can be tuned and amplified. The smallest tuned tweezers width is 0.02nm is achieved, where the number of tweezers is 10 in an array. We have also theoretically shown that the dynamic tweezers can be controlled and tuned by varies the couple coefficient (k) between 0.1-0.9 and the radius of ring resonator between 10-20 μm, which is available for trapping and transportation in the communication up-link system via a add/drop filter. In application, the transmission of tweezers with different molecules and wavelengths can be performed within the transmission link, which is available for high density molecular transportation.